2015
DOI: 10.1111/jgs.13254
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Effectiveness of Fall Prevention Programs in Nursing Homes: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials

Abstract: This meta-analysis failed to reveal a significant effect of fall prevention interventions on falls or fallers but, for the first time, showed that fall prevention interventions significantly reduced the number of recurrent fallers by 21%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(72 citation statements)
references
References 44 publications
0
63
1
Order By: Relevance
“…in older nursing home residents, the only single intervention that has reduced falls is vitamin D supplementation (20). Other interventions have been ineffective or inconsistent for falls although the rate of recurrent falls may be reduced (35). A multifactorial and interprofessional approach, determined by individual assessment of functional, medical, and social concerns, may be a more appropriate strategy to prevent falls in older people at high risk of falling (20,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)36).…”
Section: Primary and Secondary Prevention Related To Fallsmentioning
confidence: 99%
“…in older nursing home residents, the only single intervention that has reduced falls is vitamin D supplementation (20). Other interventions have been ineffective or inconsistent for falls although the rate of recurrent falls may be reduced (35). A multifactorial and interprofessional approach, determined by individual assessment of functional, medical, and social concerns, may be a more appropriate strategy to prevent falls in older people at high risk of falling (20,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)36).…”
Section: Primary and Secondary Prevention Related To Fallsmentioning
confidence: 99%
“…Preventative measures such as exercise, education and vitamin D supplements have been shown to have a non- or inconclusive effect in the residential care facility population (Avenell, Mak, & O’Connell, 2014; Bunn et al, 2014; Cameron et al, 2012). Although a review of complex multifactorial intervention programs has shown a reduction of recurrent fallers (Vlaeyen et al, 2015), there are considerable barriers for implementation outside the highly controlled circumstances of a study (Vlaeyen et al, 2017). As an alternative to active interventions, compliant flooring, defined as a flooring with some level of shock absorbency, has been suggested as a potential method for reducing the risk of fall-injuries among a frail elderly population (Lachance et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among the 108 potentially relevant publications, 59 were considered eligible for inclusion and 49 were excluded (Fig 1 and S2 Table). Twenty-eight of the included systematic reviews performed meta-analyses [3459] and thirty-one systematic reviews reported results of the included studies as a narrative summary [6091]. Fifty-seven out of 59 reviews used Pubmed to search for primary studies.…”
Section: Resultsmentioning
confidence: 99%
“…The next most frequent interventions fell under Environment in the form of environmental modifications (28 articles) [35, 3840, 45, 46, 51, 52, 5459, 63, 68, 70, 73, 74, 77, 78, 80–83, 86, 92], assistive and protective aids (24 reviews) [35, 3840, 42, 43, 45, 51, 55, 56, 58, 59, 62, 63, 68, 70, 74, 77, 78, 82, 83, 86, 93, 94], staff education (15 SRs) [35, 38, 39, 45, 49, 51, 58, 59, 70, 73, 77, 78, 82, 83, 86] and vision assessment/correction (14 articles) [35, 36, 40, 45, 51, 5559, 80–82, …”
Section: Resultsmentioning
confidence: 99%